Wideband DOA estimation based on quantum charged system search algorithm - Gao, Hongyuan; Zang, Guojian; Ma, Yuwei (International Conference on Signal Processing (Print), 2020)
An efficient wideband direction of arrival (DOA) estimation method named as CSM-ML based on maximum likelihood (ML) estimation and the coherent signal-subspace method (CSM) is mainly noticed. But the objective function of CSM-ML is multidimensional and nonlinear, and its complexity is very high. In order to solve the problems, a new optimization algorithm named as quantum charged system search (QCSS) algorithm is put forward. By means of the charged system search (CSS) algorithm and quantum optimization theory, the QCSS is developed through the designing of new quantum evolutionary equations. It has faster convergence speed, higher accuracy and it can better overcome local optimal solutions. Computer simulation indicates that the wideband DOA estimation method based on QCSS is superior to the previous wideband DOA estimation methods based on intelligence algorithms.